2021
DOI: 10.5664/jcsm.8904
|View full text |Cite
|
Sign up to set email alerts
|

Patients with epiglottic collapse showed less severe obstructive sleep apnea and good response to treatment other than continuous positive airway pressure: a case-control study of 224 patients

Abstract: The purpose of this study was to analyze patients with epiglottic collapse, especially their clinical characteristics related to obstructive sleep apnea and phenotype labeling using drug-induced sleep endoscopy. Methods: An age-sex matched case-control study was conducted to compare the clinical characteristics of patients with epiglottic collapse (Epi group) and patients without epiglottic collapse (non-Epi group). All patients underwent drug-induced sleep endoscopy January, 2015, to March, 2019, in a tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…This study highlighted an important clinical characteristic of OSA patients with a low BMI. In addition, these patients exhibited unfavourable characteristics for CPAP use [80] but demonstrated a good response to head rotation or MAD therapy [15,78].…”
Section: Tonguementioning
confidence: 96%
See 3 more Smart Citations
“…This study highlighted an important clinical characteristic of OSA patients with a low BMI. In addition, these patients exhibited unfavourable characteristics for CPAP use [80] but demonstrated a good response to head rotation or MAD therapy [15,78].…”
Section: Tonguementioning
confidence: 96%
“…The site of obstruction can be identified using DISE, and each obstruction site may be correlated with an increase in OSA severity. However, some recent studies have reported a negative cor- relation between a specific type of anatomical obstruction and OSA severity [15,73,74]. This leads to the question of whether the collapse site identified using DISE can be regarded as a phenotype predicting overall disease severity.…”
Section: Phenotype Labelling Using Dise In Osamentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with CPAP devices may aggravate airway obstruction in patients with a collapsed epiglottis [ 4 ]. Surgery in these cases could be an option [ 5 ], but it is always essential to evaluate the reason for collapse.…”
Section: Case Presentationmentioning
confidence: 99%